Effect of motor process-related priming via repeated transcranial magnetic stimulation on embodiment perception during mirror visual feedback: a pilot study - Li, Ying; Li, Ping; Li, Yixuan; Wang, Jia; Shen, Xinyao; Zhang, Mingyong; Ding, Li (Frontiers in Neuroscience, 2024)
IntroductionNon-invasive brain stimulation has been combined with mirror visual feedback (MVF) as a priming strategy to enhance therapeutic efficacy. However, a superior combined effect is hindered by the lack of emphasis on MVF-relevant embodiment perception.ObjectiveThis study assessed the priming effect of repeated transcranial magnetic stimulation (TMS) over the primary motor cortex (M1) and dorsolateral prefrontal cortex (dlPFC) on embodiment perception during MVF.MethodsIn the experiment, 15 healthy participants were required to complete tasks using their left hand while keeping their right hand static behind a mirror. They first received excitatory TMS over the left M1 or dlPFC, or sham-TMS in random order during three trial rounds and then performed three subsequent motor tasks and two task-oriented evaluations during MVF in each trial. Latency time (LT), number of embodiment occurrences, embodiment questionnaire (EQ) score, and time required to complete the task-oriented activities were recorded.ResultsThe results showed that the LT of forearm rotation in the dlPFC-TMS round was shorter than that in the sham-TMS round, although a greater number of occurrences were obtained in both the M1-TMS and dlPFC-TMS rounds compared to the sham-TMS round within the three motor tasks, which suggested that TMS priming facilitated the elicitation of embodiment perception. The EQ results indicated strengthened embodiment perception after TMS priming, especially in the dlPFC-TMS round.ConclusionThis study provides evidence that TMS priming over motor process-related regions, specifically the dlPFC, contributes to eliciting and intensifying embodiment perception during MVF, which benefited from a superior MVF paradigm for improving rehabilitation outcomes.Clinical Trial RegistrationIdentifier ChiCTR2400089499 https://www.chictr.org.cn/showproj.html?proj=240385.